Ethyl 4-acetamido-3-acetoxy-2-benzyl-3-methylbutanoate - Wang, Guang Liang (International Union of Crystallography, 2011)
The crystal structure of the title compound, C(18)H(25)NO(5), is stabilized by intermolecular N—H⋯O hydrogen bonds, which form inversion dimers. The ethyl group is disordered over two positions in a 0.651 (12):0.349 (12) ratio.